2019
DOI: 10.3389/fphys.2019.00728
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Superimposed Whole-Body Electromyostimulation During Short-Term Strength Training on Physical Fitness in Physically Active Females: A Randomized Controlled Trial

Abstract: The aim of this study was to compare the effects of short-term strength training with and without superimposed whole-body electromyostimulation (WB-EMS) on straight sprinting speed (SSS), change of direction speed (CODS), vertical and horizontal jumping, as well as on strength and power in physically active females. Twenty-two active female participants ( n = 22; mean ± SD: age: 20.5 ± 2.3 years; height: 171.9 ± 5.5 cm; body mass: 64.0 ± 8.2 kg; strength training experience 5.1 ± 3.6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…The authors observed that, except for slight improvements in some physical variables, the changes caused by the WB-EMS training were not superior to those of other exercise programs. Similar results were found by (116) in physically active women. The authors concluded that after 4 weeks of intervention, the WB-EMS training could serve as a reasonable but not superior alternative to classic training regimes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The authors observed that, except for slight improvements in some physical variables, the changes caused by the WB-EMS training were not superior to those of other exercise programs. Similar results were found by (116) in physically active women. The authors concluded that after 4 weeks of intervention, the WB-EMS training could serve as a reasonable but not superior alternative to classic training regimes.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies designed interventions whose control group carried out exercises of the same nature as the experimental group, but their training did not match the volume and frequency of training loads ( 58 , 60 , 114 , 115 ). The protocol of the present study intends to carry out an experimental phase in which the interventions of both groups are completely comparable in terms of type of movements and training volume ( 116 – 118 ). It will allow identifying precisely the isolated effect of the WB-EMS.…”
Section: Discussionmentioning
confidence: 99%
“…a Dörmann et al (2011) (5/2); Dörmann et al (2019) (0/10); Micke et al (2018) (14/7); Filipovic et al (2019) (10/0); Wirtz et al (2016) (10/0) .b Dörmann et al (2011) (5/2); Dörmann et al (2019) (0/11); Micke et al (2018) (12/4); Filipovic et al (2019) (10/0); Wirtz et al (2016) (10/0) .…”
Section: Methodsmentioning
confidence: 98%
“…Therefore, the aim of this study is to provide evidence for the effect of training with superimposed WB-EMS on lower leg strength and power as well as sprint and jump performance in trained subjects. In this regard we conducted a mini-meta-analysis focusing on individual data of 5 recent in-house WB-EMS studies (Dörmann, 2011; Wirtz et al, 2016; Micke et al, 2018; Dörmann et al, 2019; Filipovic et al, 2019). All studies were designed to characterize the impact of superimposed WB-EMS during different exercise conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Control group was assigned based on preferences and availability, whereas both intervention arms have been assigned based on coin toss. The EMS group (EG, n = 10) performed jumps with superimposed WB-EMS twice a week accompanied by 3 × 10 squat jumps in addition to the daily soccer routine over a period of 7 weeks that is a sufficient intervention period with WB-EMS to improve strength abilities [5,28,29]. To differentiate between the effects caused by EMS and by the squat jumps and soccer training respectively, two control groups were included.…”
Section: Participantsmentioning
confidence: 99%